Efektivitas Penggunaan Faktor Produksi Usahatani Anggur di Desa Kalianget, Kecamatan Seririt, Kabupaten Buleleng - GEDE MIKO SATRIA WIBAWA; I DEWA GEDE AGUNG; I KETUT SUAMBA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Effectiveness of The Usage of Production Factors in Grape Farmingat Kalianget Village, Seririt District, Buleleng Regency The existence of grapes in Bali is used as a livelihood for farmers. One of the plantationlocations that has a large number of grape vines is Kalianget Village, Seririt District,Buleleng Regency. The purpose of this study was to determine the effectiveness of theuse of grape farming production factors consisting of land, seeds, fertilizers, labor andmedicine. This research is a quantitative descriptive study by comparing the use of eachproduction factor in grape farming in Kalianget Village with the determination of theuse of grape farming production factors from the Agriculture Service. The researchsample was 47 grape farmers of Kalianget Village who were selected by purposivesampling technique. Data collection on the effectiveness of the use of farmingproduction factors was carried out with a structured questionnaire and the data wereanalyzed by Microsoft Excel computer program. The results of this study indicate thatthe effectiveness of the use of grape farming production factors in Kalianget Village,namely manure, NPK, zpt and fungicides is classified as effective. While the use ofurea, insecticides and labor is classified as ineffective. The use of several factors ingrape farming production is oriented to good and correct cultivation techniques andthere are some farmers who cannot implement it. This is because farmers do not haveenough knowledge, skills and information about good and true wine cultivation. It isexpected that farmers in carrying out agricultural activities to be more careful in the useof production factors and for the government are expected to pay attention tohorticultural products, especially wine.